Toward a dynamic process model of entrepreneurial networking under uncertainty - Engel, Yuval; Kaandorp, Mariëtte; Elfring, Tom (Journal of Business Venturing, 2017)
Although research has begun to acknowledge the strategies by which entrepreneurs form and maintain network ties, most efforts to date present an incomplete picture of entrepreneurs as heroic network architects who search, plan, and pursue contact with targeted ties. Herein, we briefly review this nascent literature, argue that it has so far overlooked alternatives in favor of an overly planned and instrumental perspective, and consider the implications of incorporating the notion of uncertainty into investigations of how entrepreneurs engage in networking. We therefore take a novel perspective on entrepreneurial networking and theorize about how entrepreneurs act when desired ties cannot be identified in advance, networking outcomes cannot be predicted, and ongoing social interactions fuel the emergence of new objectives. Overall, we add important insights to the literature, as we flesh out a dynamic networking process that unfolds alongside efforts to create a new venture. We then discuss how this model, which highlights distinctive elements such as altruism, pre-commitment, serendipity, and co-creation, can stimulate a broader research agenda focused on the inquiry of networking agency under uncertainty.